Factores asociados y tipos de lesiones oculares ocurridas en la práctica odontológica: revisión sistemática - Abanto Sheron, Jordi (2023)
Introduction: The dentist and auxiliary personnel are in constant risk of occupational diseases such as: allergies, infections, skin or eye injuries; that could affect patients. A problem of social interest are the ocular injuries that occur to dental personnel. The literature reveals the prevalence of eye injuries in dental practice that are associated with solid particles, fluid splashes. Our objective was, through a systematic review, to review the types of ocular injuries and their associated factors that occurred in dental practice. Material and Methods: The relevant studies were searched in the databases: PubMed, Scopus, Ebsco, among others. The search included cross-sectional studies that evaluated the evidence on ocular injuries occurring in dental practice, excluding literature reviews, letters to the reader, and editorials. Results: Eight studies were included to develop the systematic review; determining that the associated factors of ocular injuries occurred in dental practice are: a) occasional use of ocular protection b) age c) sex d) years of practice and the types of ocular injuries are the entry of liquids and foreign bodies. Conclusions: Deficiency in compliance with eye or facial protection protocols in dental practice, cause eye injuries; Type of fluid entry, foreign bodies, splash of biological fluids or conjunctivitis. These eye injuries are generated from associated factors such as the occasional use of eye protection, age, sex, and others.